Answer:
d. 2
Step-by-step explanation:
The average rate of change is found from ...
... (f(x2) -f(x1))/(x2 -x1) = (5 - 3)/(2 -1) = 2/1 = 2
6, 9, 9, 12, 18, 24, 24, 24, 37
37-6= 31
Answer:
1 rubber cube dude give since we'll
For the answer to the two questions above,
3x + 2y = 36.50 (I)
2x + 5y = 50 (II)
Eliminating x from the two equations by subtraction:
first we multiply equation I by 2 and equation II by 3
6x + 4y = 73
6x + 15y = 150
Subtracting the two,
-11y = -77
y = 7
He earns $7 at the coffee cart
Substituting y into equation I,
3x + 14 = 36.5
x = $7.50
So we can conclude that, he earns a greater wage of $7.50 at the library,
<span>Find the area of two sides (Length*Height)*2 sidesFind the area of adjacent sides (Width*Height)*2 sidesFind the area of ends (Length*Width)*2 ends<span>Add the three areas together to find the surface area</span></span>